The Primary Market For Securities - عبد السلام د.علي عطية (Dirasat in Economics and Business, 2002)
Primary market is where newly issued securities take place. These Securities Such as shares as shares and bonds are instruments to finance newly established companies and to provide more capital for others. They make either a public offering or special offering of these securities .public offering allows prospective investors in general to buy the securities through certain designated channels . On the other, special offering takes place through investment banks, The underwriter could either buy the whole lot of shares and sells them on a piecemeal basis to investors for a profit, or it would sell such securities for a certain commission, the first arrangement would provide the company with immediate capital which would enable it to start working as soon as possible it is imperative for the issuing company to furnish the investors with the necessary and complete financial and administrative information required for the job, so that the investors could make the proper choice. Great care should be taken in evaluating newly issued securities so that a viable financial market could be established which will channel funds to investors and promote growth in the economy at large.